2020
DOI: 10.1128/aac.00807-20
|View full text |Cite
|
Sign up to set email alerts
|

Gallic and Ellagic Acids Are Promising Adjuvants to Conventional Amphotericin B for the Treatment of Cutaneous Leishmaniasis

Abstract: In this study we demonstrated the potential association effect of conventional amphotericin B (Amph B) and Gallic acid (GA) or Ellagic acid (EA) in topical formulation for treatment of cutaneous leishmaniasis in BALB/c mice. Preliminary stability tests and in vitro drug release studies with Amph B, GA, Amph B + GA, EA and Amph B + EA in the composition and in vivo treatment of BALB/c mice infected by Leishmania major were performed. After 40 days of infection, the animals were divided into 6 groups, treated 2x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…ECGC showed similar efficacy as Glucantime, which was used as a control drug [ 108 ]. GA was tested in a topical formulation in female BALB/c mice infected with L. major and demonstrated reduction in lesion size and parasite burden [ 119 ]. The study also tested amphotericin B in a topical formulation as control drug and GA showed similar efficacy [ 119 ].…”
Section: Natural Products That Target Arginase In Leishmmentioning
confidence: 99%
See 4 more Smart Citations
“…ECGC showed similar efficacy as Glucantime, which was used as a control drug [ 108 ]. GA was tested in a topical formulation in female BALB/c mice infected with L. major and demonstrated reduction in lesion size and parasite burden [ 119 ]. The study also tested amphotericin B in a topical formulation as control drug and GA showed similar efficacy [ 119 ].…”
Section: Natural Products That Target Arginase In Leishmmentioning
confidence: 99%
“…GA was tested in a topical formulation in female BALB/c mice infected with L. major and demonstrated reduction in lesion size and parasite burden [ 119 ]. The study also tested amphotericin B in a topical formulation as control drug and GA showed similar efficacy [ 119 ]. Interestingly, the number of parasites remained lower several days after ending the treatment when GA was used; this did not occur with amphotericin B treatment [ 119 ].…”
Section: Natural Products That Target Arginase In Leishmmentioning
confidence: 99%
See 3 more Smart Citations